The enantioselective construction of chiral spirooxindole-based 4-thiazolidinone via asymmetric catalytic formal [3+2] annulation using a bifunctional catalyst. Issue 16 (2nd February 2016) - Cheng, Ping; Guo, Wengang; Chen, Ping; Liu, Yan; Du, Xin; Li, Can
Abstract : A facile and efficient method based on the asymmetric [3+2] annulation of 1, 4-dithiane-2, 5-diol to ketimines for the construction of chiral spirooxindole-based 4-thiazolidinone was reported. Abstract : 4-Thiazolidinone is regarded as a privileged structural unit in bioactive compounds. However, there is still no example of a catalytic method for the synthesis of chiral 4-thiazolidinone until now. We reported herein a facile and efficient method for the construction of chiral spirooxindole-based 4-thiazolidinone. This methodology is based on the asymmetric formal [3+2] annulation of 1, 4-dithiane-2, 5-diol to ketimines which is followed by simple oxidation, featuring a broad substrate scope with high enantioselectivity (up to 98% ee). The method has been successfully applied to the synthesis of a novel class of mycobacterium tuberculosis inhibitor-spirooxindole based 4-thiazolidinone.